The Search for Islam by Walangsungsang (Study of Historical Manuscript Analysis) - Nuraidah, Syifa; Asep Achmad Hidayat; Thohir, Ajid; Supendi, Usman (Yayasan Mentari Madani, 2023)
This research focuses on a philological study aimed at unraveling and understanding the process of Walangsungsang's search for Islam, the main character in the manuscript